Scattering from anisotropic plasma-coated PEMC cylinder buried beneath a slightly rough surface. Issue 2 (19th January 2017) - Asghar, M.; Qureshi, M. N. S.; Akhtar, M.; Fiaz, M. A.; Ashraf, M. A.
Abstract : A general theoretical formulation is done to calculate the field scattered by perfect electromagnetic conductor (PEMC) cylinder coated with anisotropic plasma material. It is buried below a slightly rough surface. Spectral plane wave representation of fields and small perturbation method are used to calculate multiple reflections between coated cylinder and rough surface. To validate the present formulation, scattered field from a PEMC cylinder coated with double negative (DNG) material is obtained from the present formulation. Scattering pattern of non coated PEC/PEMC cylinder or coated with isotropic material can also be obtained by the proper selection of physical parameters such as anisotropy, admittance of PEMC cylinder and permittivity of hosting medium. Analytical expressions of scattered field for a sinusoidal rough surface are given along with their physical interpretation to get a good insight. Effect of geometrical and physical parameters on scattering pattern is observed.